Effectiveness of a 6-week core muscle high-intensity interval training program on core stability and power in swimmers - Hiruntrakul, Ashira; Kaewwong, Tanapol; Charoensuk Kaewwong, Surumpa; Rirermkul, Parichat; Jomkokkruad, Narong; Jansupom, Charee (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. This study aimed to investigate the effectiveness of core muscle high-intensity interval training on core stability and power in swimmers.Methods. The subjects in this study were 20 male swimmers. They were randomly assigned to 2 groups by testing and sequencing the swimming speed in a 50-metre swim. The experimental group received core muscle high-intensity interval training (n = 10) in addition to their conventional training program, and the control group received a conventional swimming program (n = 10). In the experimental group, core muscle high-intensity interval training consisted of 6 main exercises that were performed 3 days/week for 6 weeks. Core stability was measured by the plank test, core power was tested by 30 and 60-second sit-ups.Results. The results of the study found that core stability from the electromyography (EMG) muscle stability test showed that the muscle activity in the m. rectus abdominis after 4 weeks and 6 weeks, the m. obliquus externus after 4 weeks, and the m. erector spine L3 after 6 weeks were significantly different in the experimental group compared to the control group (p < 0.05). Core power from the 30-second and 60-second sit-up tests in which participants performed sit-ups as quickly as possible showed that after 6 weeks, the experimental and control groups had no difference in core power.Conclusions. The results of this study showed that 6 weeks of core muscle high-intensity interval training can improve core muscle stability and power. These results can be used as information to help coaches and athletes improve the efficiency of the muscles that support swimming performance.
Keywords: swimming; muscle power; high-intensity interval training; EMG activity; core function